Impact of Peptide Sequences on Their Structure and Function: Mimicking of Virus‐Like Nanoparticles for Nucleic Acid Delivery. (24th November 2022) - Jana, Poulami; Samanta, Krishnananda; Ehlers, Martin; Zellermann, Elio; Bäcker, Sandra; Stauber, Roland H.; Schmuck, Carsten; Knauer, Shirley K.
Abstract: We rationally designed a series of amphiphilic hepta‐peptides enriched with a chemically conjugated guanidiniocarbonylpyrrole (GCP) unit at the lysine side chain. All peptides are composed of polar (GCP) and non‐polar (cyclohexyl alanine) residues but differ in their sequence periodicity, resulting in different secondary as well as supramolecular structures. CD spectra revealed the assembly of β‐sheet‐, α‐helical and random structures for peptides 1, 2 and 3, respectively. Consequently, this enabled the formation of distinct supramolecular assemblies such as fibres, nanorod‐like or spherical aggregates. Notably, all three cationic peptides are equipped with the anion‐binding GCP unit and thus possess a nucleic acid‐binding centre. However, only the helical (2 ) and the unstructured (3 ) peptide were able to assemble into small virus‐like DNA‐polyplexes and effectively deliver DNA into cells. Notably, as both peptides (2 and 3 ) were also capable of siRNA‐delivery, they could be utilized to downregulate expression of the caner‐relevant protein Survivin. Abstract : Impact of peptide sequence on structure and function : The synthetic building block guanidiniocarbonylpyrrole (GCP) is pivotal to establishing definite secondary structures out of short peptide sequences. Its rational positioning enables the assembly of different supramolecular nanostructures, like fibres, nanorods or spheres. Complexed with nucleic acids, formed virus‐like particles mediate gene delivery.